“Know your medicines, know your health”—public perspectives on medicines and health awareness campaigns - Alhomoud, Faten; Alameer, Kawthar; Almousa, Zahra’a; Almatar, Manar; Alzlaiq, Wafa; Alhomoud, Farah Kais; Alsugeir, Dana (Frontiers in Public Health, 2025)
BackgroundIrrational medication use is likely to result in therapeutic failure and disease progression. One way to increase public awareness about appropriate medication use is to design and deliver a public health medicine awareness campaign. This study aims to assess the public’s attitudes and experiences related to medication use and health awareness campaigns in Saudi Arabia.MethodsThis is a cross-sectional survey study. Participants were aged 18 or over and able to speak Arabic or English. An online survey was distributed to a convenient sample of 451 participants by email and social media via an internet link, leading to a web-based survey platform in QuestionPro. Bivariate and multivariate analyses were used to assess the associations.ResultsThree hundred and forty-seven participants (76% female, aged 18–85 years) were on a mean (SD) of two (1.86) prescription-only-medicines (POMs), and 225 were on non-prescription medicines. Seventy-one and 63 % of those surveyed consulted a doctor or a pharmacist, respectively, for advice about their medications. The participants were curious mainly about the side effects of treatment (79%), followed by drug interactions and contraindications (55%). Most participants agreed or strongly agreed that their medications were necessary to improve their condition (82%), prevent the progress of their condition (85%), and reduce the risk of complications (90%). Seventy-seven percent of participants reported seeing a public health campaign previously. TV (58%) and Twitter (55%) were reported as the most appropriate tools to help deliver a good public health campaign. Ninety-one percent believed that a public health campaign can increase people’s awareness about their lifestyle, and 73% declared that medication should be part of it.ConclusionThe findings can be a foundation for developing and implementing medicines and health awareness campaigns to enhance public understanding of health and medication use.